NATO and the South Atlantic - Carlos Gustavo Poggio Teixeira; Daniella da Silva Nogueira de Melo (Revista Conjuntura Austral, 2019)
This article contributes to the studies on NATO out-of-area operations focused on the South Atlantic. This region appeared on the organization's agenda for the first time in the 1970s, when the Soviet presence threatened the commercial maritime transport of the Western powers. After the Cold War, the Alliance has transformed its capabilities and structure in order to adapt to the events of the new international security arena by expanding its activities beyond the North Atlantic borders. Partnership agreements with Colombia and Mauritania, joint military exercises with Cape Verde, Ghana and other West African countries evidence NATO projection in the South Atlantic. In addition, the article exposes the abundance of natural resources, threats to security and the growing projection of extraregional actors (Russia, China and India) as likely factors for NATO engagement in the region.